Facebook engagement in Malaysian Ministry 2024 - Zaki Mustafa, Muhamad; Raqib Mohd Sofian, Muhammad; Ahmad Sabri, Safiyyah; Yahya Mohd Ariffin, Mohd; Faizal Kasmani, Mohd (Universitas Ahmad Dahlan, 2025)
In the era of digital governance, social media platforms, particularly Facebook, have become essential tools for government communication and public engagement. This study examines the dynamics of Facebook usage within selected Malaysian Ministries, focusing on objectives, strategies, and outcomes of engagement. The research aims to identify the ministries’ communication goals and analyze the types of content that elicit the highest audience interaction. Employing a quantitative content analysis, 3,902 Facebook posts published between January and June 2023 were analyzed across three ministries: the Ministry of Communication and Digital, the Ministry of Home Affairs, and the Ministry of Women, Family, and Community Development. Data on likes, comments, shares, and post characteristics were systematically coded and assessed using SPSS. The findings reveal that the majority of posts adopt a one-way Public Information model, with limited evidence of two-way symmetrical communication. Engagement was highest in the Ministry of Communication and Digital, where posts generated over 115,000 likes and 53,000 shares, while the other ministries recorded substantially lower interactions. Content emphasizing public announcements and informational updates attracted the most responses, whereas dialogic communication remained minimal. This study contributes to the understanding of how government agencies in emerging economies utilize social media as a strategic communication tool, highlighting both strengths and gaps in fostering meaningful two-way interaction. The results underscore the need for ministries to enhance dialogic strategies to strengthen trust, responsiveness, and citizen participation in digital governance.